A study of oropharyngeal parasites infection in doves and domestic pigeons in some villages of Garmian -Iraqi Kurdistan region - Wahhab, Mohammed Abdulkareem; Abdulrahman, Nawzad Rasheed; Ali, Shahnaz Abel-Kader (Kurdistan Journal of Applied Research, 2017)
The present study was performed in Garmian area-Iraqi Kurdistan Region on doves and domestic pigeons (Columbids) which were collected during the period from the1st of December 2015 to 30th April 2016 to study the naturally occurring of oropharyngeal parasites and their prevalence rates of infections. The wet samples were swabbed from oral cavity and pharyngeal region of all birds, and then screened by wet mount searching for parasites. The results of the current study revealed that only one species of protozoan parasite was identified which was Trichomonas gallinae. The results also showed that the total prevalence rate of infection from the total number of examined birds (249) was 54 (21.69%). Out of the 142 doves (63 males and 79 females) and 107 domestic pigeons (62 males and 45 females) examined, 29 (20.42%) doves [13 (20.63%) males and 16 (20.25%) females)] and 25 (23.36%) domestic pigeons [15 (24.19%) males and 10 (22.22%) females) were infected with T. gallinae protozoon parasite. In the present study it was found that the two examined bird species were infected with this protozoon and there was a gradual rise in prevalence of infection from beginning to end of the study. Small variations in the prevalence rate of T. gallinae infection between doves (20.42%) and domestic pigeons (23.36%) were observed but this variation not reached to the level of statistical significance (P >0.05). It is worthy to note that in all of the infected birds in the study Trichomoniasis occurred without observation of any apparent secondary diseases or signs. In conclusion Trichomoniasis is less common in urban doves and domestic pigeons in Garmian area, Kurdistan Region- Iraq. Further research is suggested in relation to protozoan parasite in other bird species in a study will be conducted in all months of the year to find the reasons which affect the prevalence rate of infection and to estimate the parasite-host relationship.